Keabsahan Perjanjian Elektronik Sebagai Akta di Bawah Tangan dalam Perspektif Kuh Perdata dan Undang Undang Nomor 11 Tahun 2008 Tentang Informasi dan Transaksi Elektronik - Winta Hayati (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2026)
The growth of digital transactions in Indonesia has raised important legal questions about the status of electronic agreements. Data from APJII (2024) shows that internet users in Indonesia reached 221 million people, while BPS (2023) recorded national e-commerce transactions at Rp 476.3 trillion in 2022. These figures indicate that electronic agreements have become a primary instrument in everyday legal interactions. This study aims to analyze: (1) whether an electronic agreement can be categorized as a private deed (akta di bawah tangan) as stipulated under Article 1874 of the Indonesian Civil Code in conjunction with Articles 5 and 11 of Law Number 11 of 2008 on Electronic Information and Transactions (UU ITE); and (2) the evidentiary strength of electronic agreements as private deeds in court proceedings. Using normative legal research with statutory, conceptual, and case approaches, this study finds that electronic agreements fulfill the requirements of a private deed when they contain an electronic document recognizable under Article 5 UU ITE and a certified electronic signature meeting the requirements of Article 11 UU ITE. As to evidentiary strength, the electronic agreement has perfect evidentiary force when acknowledged by the opposing party under Article 1875 of the Civil Code, but is subject to further verification when disputed. The study recommends harmonization between the Civil Code and UU ITE, and institutional strengthening of electronic certification bodies.